Does Micro Waqf Bank Avoid Loan Sharks Practice? Keeping on Indigent Productive Business - Muhamad Fauzi; Junaedi; Mahmudin (International Economic and Finance Review, 2023)
The Holy Qur'an reminds Muslims to conduct lawful economic activities to get the common good. The indigent with small and micro businesses are constantly faced with financing constraints, so the presence of Islamic microfinance institutions can provide this convenience. This study analyzes the role of micro waqf banks in preventing their customers from the loan shark practice. The study uses a qualitative method with an exploratory approach to micro waqf bank customers in the province of Banten. Data collection is sourced from interviews, observations, and literature studies, while data analysis uses triangulation techniques. The results are that most of the customers of micro waqf banks had transacted with loan sharks before becoming members of micro waqf banks. Micro waqf bank aims to provide financing, guidance, and business empowerment for poor productive communities around Islamic boarding schools. They are increasing the role of micro waqf banks, namely increasing weekly halaqah, inviting and reminding not to transact with moneylenders, increasing Islamic financial literacy, helping each other among group members, and disseminating product information. The avoiding effort of loan shark practice by increasing access to sharia finance, obtaining loans through individuals or mosques without usury, selling owned goods and cohesiveness between group members or joint responsibility, Efforts to increase productive businesses, namely product innovation and marketing, increasing the number of business products and business training. The implication is that increasing micro waqf banks' roles can prevent customers from using loan sharks in business and not entering deeper indigent. Keywords: Avoiding, Indigent, Loan Shark, Micro Waqf Bank, Productive Business